BR-440 in Juiz de Fora (MG) and its developments: A narrative revision analysis (Research, Society and Development, 2021)
The construction process of the BR-440 in Juiz de Fora - MG is valid for a considerable period of time (twelve years). The work, which began in 2009, which is the responsibility of the National Department of Infrastructure and Transport (DNIT in portuguese), still faces obstacles to its completion, mainly due to environmental issues related to the layout of the road and the channeling and coverage of the São Pedro stream, fostering debates about its real benefit to the municipality. Thus, the objective of this article is to discuss (i) the insertion of BR-440 in the current context and (ii) how the referred infrastructure is perceived by the local population, as well as by those who acted in its implementation. The study was based on a narrative revision analysis, based on news from the local newspaper Tribuna de Minas, through an analysis of reports published over the last decade that raise technical and social discussions about the construction of the highway. The results show that the problems arising from its construction still generate many legal and political discussions, as well as inconvenience to the population that lives close to the road.